Development of polymeric microelectronics packaging encapsulation for harsh environment applications - Phua, Eric Jian Rong (Nanyang Technological University, 2018)
Epoxy has been the choice of mainstream polymer encapsulation in electronics packaging since the 1960s. Many present electronic applications require polymer materials which are stronger mechanically and functions at higher temperature due to increasing operation demands. Research was previously conducted on a polymer alternative known as phthalonitrile (PN) in the form of structural material but little work has been carried out in the use of phthalonitrile as an electronic packaging material. Inspired by the extensive usage of epoxies, we propose that the low melting temperature resorcinol based phthalonitriles (PN) can be cured to form new high temperature composites reinforced by silica and alumina fillers that may be used and acceptable in the microelectronics packaging facilities. In this thesis, the strategy is to evaluate and propose utilization of the new composite which comprises of strong covalent bonds between the matrix and its proposed fillers proven by both Fourier transform infrared spectroscopy (FTIR) and Density Functional Theory (DFT) analysis. PN can be cured to temperatures higher than 300°C and is a crucial binder in the proposed encapsulant and die attach material for further investigation. This is the first treatise which extensively evaluates PN as an electronic material suitable for both bonding and as an encapsulant substitute for epoxy. Thermal degradation studies revealed that PN or its filled composites can sustain to temperatures 400°C and beyond. Mechanical characterizations reveal that PN and its filled composites do not encounter sudden failures when temperature is being elevated to 300°C. Other properties such as Coefficient of Thermal Expansion (CTE) can be tuned with fillers such as silica and alumina to match underlying substrates. Dielectric constants show that with 50 weight percent silica, it is possible to obtain dielectric constants of 3.99 which makes a filled version of PN highly comparable to existing epoxy molding compounds (EMC) that are filled with higher loadings of silica of up to 90 weight percent. Systematic studies have also been implemented to study PN integrated with 24-pin standard alumina Dual in-line Package (DIP). Further High Pressure High Temperature (HPHT) integrated testing reveals that 50 weight percent silica filled PN can survive up to a maximum pressure and temperature of 190 MPa and 310°C respectively, because of the unique thermomechanical strength imparted from its molecular structure. Lastly, dome shaped polymer encapsulation designs are studied and enhanced using Workbench or SolidWorks™. These designs are then imported into ANSYS™ mechanical solvers for structural and thermal evaluation using coupled multi-physics studies. In conclusion, the integration of PN into electronic packages for harsh environment applications has been demonstrated through simulations and prototype testing.